(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2019)
In the cubist expression of the early twentieth century, thought begins to play a fundamental role in the creative process. The reason lies in the fact that it is a revolution of thought, even before an aesthetic revolution. It is the basic concept that changes, thanks to the reflection that, unknowingly or not, it takes its moves from the thought of men of the past, including Augustine, Plato, Aristotle, Descartes, but also Husserl, Hildebrand, Bergson. This is because every human expression is the result of concepts studied and observed, deepened and challenged. The sculpture was, however, part of the great revolution in art history just as much as painting, due to the work of some artists including Picasso, Boccioni, Brancusi, Archipenko, Gaudier-Brzeska, Lipchitz, Nadelman and Duchamp-Villon. In the particular case of the cubist sculptors, the expressive solutions they adopt are consequent to a new way of implying the world and the intellectualistic phenomena that accompany its evolution. Keywords: Cubism; Phenomenology of Cubism; Cubist painting; Cubist sculpture.